Trente-cinq tableaux inédits de Théophile Hamel - Vézina, Raymond (RACAR : Revue d'art canadienne / Canadian Art Review, 1982)
Thirty-five paintings executed by Théophile Hamel for the Canadian government are reproduced here for the first time. Various authors from 1922 up to 1970 insisted that these paintings had been destroyed in fires in governments buildings. This mistake was rectified in 1970 by R. H. Hubbard. In 1975 and 1976, R. V. published the catalogue of the paintings including their location. Problems related to their size and the reflections in the glass panes covering them prevented their being photographed before 1981.The ‘Information on the subject’ which accompanies the photographs conforms to the norms set down in the method developed by the author for the computerized inventory of works of art. To ensure the accuracy of the information presented, verifications were made in a pre-established list of dictionaries and specialized publications. The information is presented under three headings: sources, disallowed information, and accepted information. The numbers refer to the sources confirming or refuting the information under each heading. The ‘Information on the paintings’ were taken straight from the paintings themselves. Written permission from one of the institutions housing these paintings is required in order to obtain a photograph from the Picture Division of the Public Archives of Canada.